A New Recast of Gödel's Ontological Argument in Hájek’s Language - Mohammad Maarefi; Mohsen Feyzbakhsh (پژوهشنامه فلسفه دین, 2016)
Since 1970, when Gödel tried to provide a new articulation of the so called ontological argument, many considerable discussions has been emerged due to assessment of his argument's validity and soundness. For example, Sobel tries to show some defects of Gödel's argument. Petr Hájek, the eminent logician and mathematician, tries to save this argument from Sobel's critiques by some small amendments. According to him, if we articulate this argument in S5 system of modal logic with a few changes, we can have a safe argument. Besides, Hájek believes that this argument is of little interest from theological perspective. In this article, after a survey of Hájek’s work, we shall try to put this later claim under scrutiny and show the theological relevance of the argument. Finally, we show that despite the fact that Hájek and many other logicians consider Gödel's argument just as a "formal model" of an ancient argument, this argument seems a bona fide and justified argument for God’s existence.